Penerapan Model Problem Based Learning Berbantuan Powerpoint untuk Meningkatkan Motivasi Belajar Kelas 2 SD - Jamal, Ahmad Badrul; Abduh, Muhammad; Lestari, Sri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This study is motivated by the reality that currently students' high-level thinking skills have not been achieved and their learning motivation is low. Even though students are expected to be able to overcome their difficulties with the help of 4C skills. Low motivation to learn is undoubtedly an important problem in education, where educators must take a leading position. Teachers should incorporate more activities into the classroom. The approach or model used by the teacher clearly has an impact on student actions. If teachers involve students in lessons, they will study harder, and vice versa. The aim of this research is to increase student learning motivation with the PBL model assisted by PPT media. This type of research is classroom action research (PTK) with research subjects of 24 class 2D students at SDIT Nur Hidayah. This research shows that the PBL model assisted by PPT media can increase students' learning motivation. The first cycle has a percentage value of 60%. Meanwhile, cycle II has a percentage value of 74%. Therefore, there was an increase from cycle I to cycle II, namely 14%.